2021
DOI: 10.3892/ijmm.2021.5039
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis of long non‑coding RNA expression profiles induced by resveratrol and metformin treatment for hepatic insulin resistance

Abstract: Resveratrol (RSV) and metformin (MET) play a role in the treatment of diabetes; however, the mechanisms through which they mediate insulin resistance by regulating long non-coding RNAs (lncRNAs) remain unknown. The present study was conducted to determine whether RSV and MET can improve insulin resistance in the livers of high-fat diet (HFD)-fed mice by regulating lncRNAs. C57BL/6J mice were fed a HFD for 8 weeks to establish a model of insulin resistance. The mice were subsequently treated with RSV or MET for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…Studies have shown that 456 lncRNAs are upregulated and 409 lncRNAs are downregulated by cAMP stimuli, and nearly half of them are attenuated by metformin treatment 45 . Another study also showed a similar result, in which metformin and resveratrol treatment altered lncRNA profiles in the livers of obese mice, and those lncRNAs regulate insulin signaling pathways 46 . Thus, metformin treatment may exert its antidiabetic effect by altering lncRNA expression.…”
Section: Roles Of Lncrnas In Diabetesmentioning
confidence: 78%
“…Studies have shown that 456 lncRNAs are upregulated and 409 lncRNAs are downregulated by cAMP stimuli, and nearly half of them are attenuated by metformin treatment 45 . Another study also showed a similar result, in which metformin and resveratrol treatment altered lncRNA profiles in the livers of obese mice, and those lncRNAs regulate insulin signaling pathways 46 . Thus, metformin treatment may exert its antidiabetic effect by altering lncRNA expression.…”
Section: Roles Of Lncrnas In Diabetesmentioning
confidence: 78%
“…Mice lncRNAs have been previously associated with metformin treatment accessed by RT-qPCR and microarray analyses [ 74 , 75 , 76 ]. Nevertheless, these types of analyses do not allow isoform-specific evaluation due to technical limitations and also because of the less extensive ncRNA annotation of mouse if compared to human genome.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that resveratrol and metformin (MET), a first-line drug for the management of type 2 diabetes ( Giannarelli et al, 2003 ), exert glucose-lowering effects through similar mechanisms, i.e., reduced hepatic gluconeogenesis, inflammation and oxidative stress, mainly through the activation of NAD-dependent deacetylase SIRT1 and AMP-activated protein kinase (AMPK) ( Dludla et al, 2020 ). Based on this finding, a study has sought to determine whether such effects are mediated by lncRNAs, performing a comparative analysis of liver tissue lncRNAs expression profiles by high-throughput sequencing from high-fat diet (HFD)-fed mice treated with resveratrol and MET ( Shu et al, 2021 ). Both compounds attenuated liver insulin resistance by regulating lncRNAs, although MET exerted a more prominent effect.…”
Section: Insulin Resistance Diabetes and Obesitymentioning
confidence: 99%
“…Both compounds attenuated liver insulin resistance by regulating lncRNAs, although MET exerted a more prominent effect. Moreover, both resveratrol and MET affected the PI3K/Akt signaling pathway through the NONMMUT034936.2 and G6PC target genes ( Shu et al, 2021 ). By using the same experimental model (HFD-fed mice), another study identified mmu-miR-363-3p as the major miRNA involved in the beneficial effects of resveratrol on insulin resistance.…”
Section: Insulin Resistance Diabetes and Obesitymentioning
confidence: 99%
See 1 more Smart Citation